Foraminiferal micropaleontology of the Harami Formation (Elazig, Eastern Turkey), and reassessment of its age based on larger benthic foraminifera - Kaygili, Sibel (Tubitak Scientific & Technological Research Council Turkey, 2023)
The age and depositional environment of the Harami Formation were reevaluated based on the new larger benthic foraminiferal (LBF) data. LBF assemblage including Orbitoides medius (d'Archiac), O. megaloformis Papp and Kupper, O. gruenbachensis Papp, Pseudomphalocyclus blumenthali Meric, Omphalocyclus macroporus (Lamarck), Sirtina cf. orbitoidiformis Bronnimann and Wirz, Hellenocyclina beotica Reichel, Lepidorbitoides campaniensis Van Gorsel, L. bisambergensis (Jaeger), L. cf. minor (Schlumberger), Pseudosiderolites vidali (Douville), and Siderolites gr. calcitrapoides Lamarck were determined in the formation. Based on this LBF assemblage data, the late Campanian-Maastrichtian age was assigned to the formation. The paleontological and sedimentological data indicate that the Harami Formation was deposited on a shallow ramp environment.
Keywords: Harami Formation; late Campanian-Maastrichtian; eastern Turkey; Elazig